Penggunaan QRIS sebagai Alat Inovasi Digital Keberagaman dan Kesejahteraan Ekonomi UMKM Pudakpayung Semarang - Sania Rizqiatur Rohmah; Vonny Aurellya Pratama; Mohammad Yamin Darsyah; Eka Dimas Kartika Robiatul Adawiyah; Gustan Alnadsyah; Irfan Noor Syabana; Novi Anisa Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia's economic and social transformation has been significantly reinforced by the implementation of the Quick Response Code Indonesian Standard (QRIS) through digitalization. This research investigates the impact of the implementation of QRIS on the digitalization of MSMEs in the promotion of religious moderation and the establishment of social harmony. This research discovered that the adoption of QRIS not only enhances transaction efficiency and financial inclusion, but also fortifies social interactions among individuals from a variety of backgrounds, through surveys and direct assistance to 30 MSMEs in Pudakpayunh Village. The findings indicate that QRIS plays a role in the reduction of economic inequality, the enhancement of welfare, and the reinforcement of ethical values in business, all of which contribute to the establishment of a more harmonious and moderate social life. As a result, the implementation of QRIS is not only pertinent in an economic context, but also as a means of enhancing social cohesion and diversity in Indonesia.